Ανοιχτή χαρτογράφηση: η πόλη ως προς πολλαπλά υποκείμενα - Stamatopoulou, Athina (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αρχιτεκτόνων Μηχανικών, 2016)
The thesis 'Open Mapping: The City in regard to multiple subjects' deals with the mapping of the city in the context of an urban design process. Considering the city as a multiple, constantly changing and open object in regard to the multiple subjects, from which it is being created, as well as triggered by concerns about the urban design process, our hypothesis arises along with a question: how can we integrate the multiplicity of the city in regard to its subjects in an intervention or a design or a management process in/ of the city? We argue that a mapping of the city may not only contribute to such an integration of the subjects, but it can go beyond, towards our broader aim: it may function as a tool of managing the city’s complexity, that emerges from the multiplicity of its subjects. Being articulated by the inquiry of how we could find such a mapping tool, our object of research focuses on its construction; on the construction of a method - a tool of an open mapping of the city. The openness, concerning both content and method, is a central feature of the tool. Specifically, the construction is based on an open scheme constituted by three mutually composed levels of actions. The first concerns the collection of different mappings of the city made by different subjects. The second explores possible interrelations/ connections and synergies among the collected mappings. The third consists of mapping experiments as well as of calls for applications of the method’s logic, triggering the emergence of further ways - new schemes - of open mapping. Doing a specific experiment and addressing one call for application, we reveal third level’s capability to evolve - in terms of feedback and of broadening - the logic of mapping, which we construct. In this way, the third level - through every experiment and every call - challenges what kind of mapping we are constructing and how we do that; it provokes redefinition(s) of its features, its purposes and its logic according to its specific context. Through the process of constructing such a method-in-a-constant-dialogue-with-actions, we highlight the creative perspective of a mapping, while exploring transition paths towards the logic of managing the city; the city considered as constituted by multiple material and non-material relationships, constantly emerging and changing without ending.